IMPLEMENTASI KONSTITUSI REPUBLIK INDONESIA PERSPEKTIF PERTAHANAN NEGARA - Sopamena, Chairussani Abbas (Jurnal Academia Praja, 2025)
This research aims to describe the implementation of the 1945 Constitution, the State Constitution and the highest source of law in the Republic of Indonesia from the perspective of national defense. Its formulation coincided with the birth of Pancasila on June 1 1945 at the first BPUPKI session. The formulation of the Constitution began on July 10 1945 with the start of the second BPUPKI session to draft the constitution. The 1945 Constitution was officially implemented as the Indonesian state constitution by PPKI on August 18 1945. In Chapter XII Article 30 regulates the state agriculture and security system, especially regarding the Indonesian National Army (TNI). Referring to the 1945 Constitution, UU RI No. 3 of 2002 concerning National Defense was established in the State Gazette of the Republic of Indonesia of 2002 Number 3 where it is explained about the TNI with its elements, namely: Army, Navy, and Air Force with the main task, namely paragraph (2).